ICH Q8 Guidelines in Practice: Spray Drying Process Optimization by 23 Factorial Design for the Production of Famotidine Nanoparticles - Ayre, Anita; Lalitha, K.G.; Ruckmani, K.; Khutle, Nilesh; Pawar, Harshal; Dand, Neha; C, Vijaya (Pharmaceutical Nanotechnology, 2014)
Keeping in view the standpoint of quality by design, the current work was undertaken to optimize the process parameters in spray drying involved in the production of nanoparticles of famotidine (FAM), a drug with low oral bioavailability. Statistical experimentation approach using 23 full factorial design was utilized to optimize the spray drying process variables. Polymeric PLGA nanoparticles of FAM were formulated employing spontaneous emulsification-solvent diffusion technique. The critical process parameters (CPPs) chosen were the inlet temperature, the feed rate of the liquid and the aspiration flow rate. The influence of these CPPs on the critical quality attributes (CQAs) like % yield of the dried nanoparticles, was studied. Predicted conditions for maximum yield were: inlet temperature 150 °C, feed flow rate 4.5mL/min and aspiration airflow rate at 1490rpm which led to a yield of 52.6±0.4%. The spray dried nanoparticles were characterized for yield, size, zeta potential, morphology, in vitro drug release and mucoadhesion ability. A comparative analysis of the formed nanoparticles was done with the plain drug and excipients using XRD, DSC and FTIR techniques. The average particle size of the dried nanoparticles was found to be 324±4nm. The polydispersity index was 0.739±0.085. The release of drug from the polymeric nanoparticles followed Higuchi square root kinetics. Thus the use of statistical designing of experiment in the domain of the optimization of spray drying technique was proved to be effective to obtain spray dried nanoparticles of FAM with an appreciable yield.
Keywords: 23 factorial design